2-Amino-1-methyl-6-phenylimidazo[4, 5-b]pyridine (PhIP) formation and fate: an example of the coordinate contribution of lipid oxidation and Maillard reaction to the production and elimination of processing-related food toxicants. Issue 13 (14th February 2015) - Zamora, Rosario; Hidalgo, Francisco J.
<x xml:space="preserve">Abstract</x> Major chemical reactions dealing with carbonyl chemistry in foods (Maillard reaction and lipid oxidation) play a role in PhIP formation and fate, pointing to this and analogous heterocyclic aromatic amines as outcomes of this chemistry.